2014
DOI: 10.1142/s1793292014500180
|View full text |Cite
|
Sign up to set email alerts
|

HIGH-PERFORMANCE Pt/CNTs CATALYSTS VIA HYDROGEN PLASMA FOR METHANOL ELECTROOXIDATION

Abstract: High-performance carbon nanotubes-supported Pt catalysts (Pt/CNTs) catalysts were prepared on the basis of Pt precursors reduced by hydrogen plasma (Pt/CNTs-HP) generated by microwave. The other two Pt/CNTs catalysts prepared by hydrogen (Pt/CNTs-H) and NaBH 4 (Pt/CNTs-N) reduction were also involved for comparison. The practical composition of the catalysts was characterized with energy dispersive analysis of X-ray (EDAX). It was shown from transmission electron microscopy (TEM) and X-ray di®raction (XRD) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…By contrast, Xu et al [21] found that Pt nanoparticles in Pt/CNTs-HP prepared by H 2 plasma reduction of Pt-based precursor showed more uniform distribution on CNT with the particle size of about 2 nm. They had better MOR electrocatalytic activity than a traditional hydrogen reduced catalyst (Pt/CNTs-H) and NaBH 4 reduced catalyst (Pt/CNTs-N).…”
Section: Noble Metal Electrocatalystsmentioning
confidence: 93%
“…By contrast, Xu et al [21] found that Pt nanoparticles in Pt/CNTs-HP prepared by H 2 plasma reduction of Pt-based precursor showed more uniform distribution on CNT with the particle size of about 2 nm. They had better MOR electrocatalytic activity than a traditional hydrogen reduced catalyst (Pt/CNTs-H) and NaBH 4 reduced catalyst (Pt/CNTs-N).…”
Section: Noble Metal Electrocatalystsmentioning
confidence: 93%
“…Currently, some significant breakthroughs have been made concerning nanostructured carbon composite material in electrochemical sensors [19], catalysts [20,21,22,23], and supercapacitors [24]. Additionally, many ceria–carbon composites have been reported, such as CeO 2 /graphene [25], CeO 2 /g–C 3 N 4 [26], and MWCNTs/CeO 2 [27].…”
Section: Introductionmentioning
confidence: 99%